Science, Technology, Engineering, Arts, and Mathematics Project-Based Learning in Environmental Education: A Systematic Review - Arif Widiyatmoko; Rahina Nugrahani; Hutkemri Zulnaidi; Rizki Nor Amelia; Trida Ridho Fariz; Nadia Eka Ardhani; Tiara Dwi Wulandari (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Environmental education requires a contextual and active learning approach that connects environmental issues to students’ learning experiences. This study aims to systematically review the implementation of science, technology, engineering, arts, and mathematics into project-based learning (STEAM-PjBL) in environmental education. Articles were collected from the scopus, web of science, eric, and google scholar databases for the period 2016-2026, following the PRISMA guidelines. A total of 19 articles met the inclusion criteria and were analyzed using a narrative-thematic approach. The review results indicate that STEAM-PjBL is widely implemented across various educational levels through contextual projects, such as plastic recycling, waste management, eco-enzymes, ecobricks, waste-to-energy, sustainable cities, SDG-based projects, and ethno-STEM. The findings indicate that STEAM-PjBL contributes positively to environmental literacy, particularly in terms of environmental knowledge, cognitive skills, attitudes, and behavior. However, climate change-related attitudes still tend to emerge more indirectly through environmental concern, awareness, sustainability, responsibility, and intention to act, rather than through explicit measures of climate change beliefs and intentions. This review supports educators, researchers, and curriculum developers in designing more contextual, practical, and sustainability-oriented STEAM-PjBL learning.